Bengoa, J. (editor), Territorios rurales. Movimientos sociales y desarrollo territorial rural en América Latina - Fernando Romero (Estudios Económicos, 2007)
Bengoa, J. (editor), Territorios rurales. Movimientos sociales y desarrollo territorial rural en América Latina